Design of Solar Rooftop Using Helioscope in The Gazebo of Pelabuhan Ratu Coal Power Plant - Bayu Indrawan; Aryo De Wibowo Muhammad Sidik; Anggy Pradiftha Junfithrana; Marina Artiyasa; Ilman Himawan Kusumah; Andika Kurniawan (Universitas Nusa Putra, 2023)
Research on simulating the design of a solar power plant in the village of Wantilan Antosari aims to promote the use of new renewable energy sources. The method of PLTS is completed by paying attention to and accounting for the tilt angle in the Helioscope Software, designing the positioning of solar panel modules, designing inverters, configuring circuits, accounting for the number of batteries used, choosing Battery Control Units, and calculating investment. According to the simulation run by the helioscope program, nine solar modules at an angle of 58.7 can power a battery with a 500Ah capacity. The simulation also establishes an inverter with a 24.06kW inverter that generates 4.0 kWp power.